A fault-tolerant algorithm of AUV formation based on reconfiguration map - Gao, Peiyan; Li, Yiping; Li, Liang; Zhang, Yuexing; Wang, Hailin; Xu, Gaopeng; Li, Shuo (Ocean engineering, 2024)
Aiming at the fault occurrence of AUV formation members during sailing, a fault tolerance algorithm of AUV formation based on reconfiguration was proposed. Firstly, the cost matrix is designed based on the reconfiguration and Hungarian algorithm to solve the problem of assigning target points under the fault condition. Then, based on Bezier curves, the dynamic constraints of AUV are designed parametrically. The nonlinear optimization problem satisfies the constraints through the characteristics of spline curves, and the adaptive particle swarm optimization algorithm is used to solve the tracking trajectory. The comparison and simulation experiment of a particle swarm algorithm based on a reconfiguration map (RMPSO) was carried out. The simulation results show that under the same planned path, the total tracking path of the following AUV is shorter, the turning radius is smaller, and the heading Angle is more stable. Finally, field tests are carried out in Qiandao Lake to verify the effectiveness of the algorithm for formation faults. •Proposed a fault tolerance algorithm for AUV formation based on reconfiguration, using the Hungarian algorithm for fault condition target assignment.•Designed AUV dynamic constraints parametrically with Bezier curves, satisfying conditions through nonlinear optimization.•Employed adaptive particle swarm optimization to solve the tracking trajectory issue, validating the algorithm's efficiency through simulation experiments on the MOOS-IvP platform.•Field tests in Qiandao Lake confirmed the algorithm's effectiveness in handling formation faults.